2017
DOI: 10.1155/2017/6824051
|View full text |Cite
|
Sign up to set email alerts
|

Land Cover Information Extraction Based on Daily NDVI Time Series and Multiclassifier Combination

Abstract: A timely and accurate understanding of land cover change has great significance in management of area resources. To explore the application of a daily normalized difference vegetation index (NDVI) time series in land cover classification, the present study used HJ-1 data to derive a daily NDVI time series by pretreatment. Different classifiers were then applied to classify the daily NDVI time series. Finally, the daily NDVI time series were classified based on multiclassifier combination. The results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…Another related study proposed a new method for classifying daily NDVI time series data based on a combination of multi-classifiers ( Zhao et al, 2017 ). In this study, the HJ–CCD satellite was used as data for compiling an NDVI time series model with S–G filtering and spatial interpolation.…”
Section: Related Workmentioning
confidence: 99%
“…Another related study proposed a new method for classifying daily NDVI time series data based on a combination of multi-classifiers ( Zhao et al, 2017 ). In this study, the HJ–CCD satellite was used as data for compiling an NDVI time series model with S–G filtering and spatial interpolation.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have revealed that multi-temporal remotely sensed data provide the distinctions between similar spectral of different land cover types (de Bie et al 2011;Miomir et al 2018;Usman et al 2015). Generally, NDVI values range from -1 to +1 (La et al 1987;Zhao et al 2017), where surface features like water, snow and cloud reflect more in the visible band than in the near-infrared band, thus represented as negative NDVI values.…”
Section: Image Pre-processing and Ndvi Generationmentioning
confidence: 99%
“…Once the process of image correction was completed, 80 covariates were generated based on the Landsat annual composites, and SRTM DEM was then used as input to supervise the classification. Thus, the image indices collectively provided a critical parameter for classifying land cover, and this has a noticeable correlation with the particular land cover association (Zhao et al 2017;da Silva et al 2019).…”
Section: Satellite Image Processing and Land Cover Mappingmentioning
confidence: 99%